A Survey of Object Detection Methodologies Based on Deep Learning: A Comparative Study of Object Detection Methodologies Based on Deep Learning (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In past couple of years, it has been observed that digital data is accumulating with astronomical speed. Every day people have been clicking and sharing numerous images with each other. Moreover, video surveillance, vision based security system keep on gathering the raw footage every second. To extract out the desired information from these raw data automatically and precisely in real time, various method has been implemented.This paper present the comparative study of various methodologies based on deep learning to extract out the desired information from images specifically detection of object from image. Object detection has broad spectrum of application in various artificial intelligence based industry. So it plays a vital role in current technical era.